Seric IgG anti-SARS-CoV-2 pre- and post- Covid-19 pandemic from Mexican asymptomatic subjects - Lucinda Aguirre-Cruz; Martín Guzmán-García; Isaac Acosta-Castillo; Dora L de la Cruz-Aguilera; Isabel Landero-Isidro; Juana P. Pérez-González; Jaqueline Chávez-Duarte; Adolfo Leyva-Rendón (Instituto Nacional de Salud Pública, 2022)
Objective. To detect serum IgG anti-SARS-CoV-2 in pre-and post- Covid-19 pandemic in Mexican asymptomatic subjects in order to know the degree of viral dispersion. Materials and methods. Association of serum IgG antibodies (determined by ELISA) to sociodemographic and clinical data or contact with Covid-19 cases in three groups of subjects: 1) Covid-19 pre-pandemic blood donors (n= 538); 2) Covid-19 post-pandemic blood donors (n= 243); 3) Covid-19 post-pandemic neurological patients (n= 312). None of the subjects studied had been vaccinated. Results. The positive rate of IgG anti-SARS-CoV-2 was notably higher in participants recruited during the pandemic (donors, 29.6%; neurological patients, 15.7%) than in those recruited pre-pandemic (donors 0.6%) (p <0.001). Other conditions associated to antibody positivity were being a worker in sales or services, or having had previous contact with people with Covid-19, for donnors and neurological patients, and having diabetes mellitus, for neurological patients. Higher positivity levels of anti-SARS-CoV-2 IgG were found in females than in males. The highest proportion of subjects with anti-SARS-CoV-2 antibodies was found in central Mexico. Conclusions. The dispersion of SARS-CoV-2 in asymptomatic, unvaccinated subjects (donors and neurological patients) recruited in a Mexican health institution, who work in sales or services or had previously had contact with Covid-19 patients is 16 to 30%. The level of positivity for anti-SARS-CoV-2 IgG is higher in females than in males. SARS-CoV-2 antibody seroprevalence follow-up studies must be favored among the general population, being mandatory for donors.